Opis kozarjeve skodele v Teokritovi Prvi idili - Lamut, Ana Marija (Ars et humanitas, 2017)
Rather than mere decoration, the description of the cup inserted into the First Idyll by Theocritus is an integral part of the poem, as there is no clear-cut line separating the description from the main narrative. The cup is said to be made of wood, with three linear carvings on the outside. The first carving presents two men vying for a woman's favour, the second an old fisherman, and the third a boy in a vineyard, weaving a net for locusts. Since the rivalry and vineyard scenes are also found on the shield of Achilles, these motifs and the style of the description appear to draw on an older tradition in poetry. My analysis of the text is set in the framework of ekphrasis, a rhetorical technique defined in Ancient Greek rhetorical handbooks as "a descriptive speech that brings the subject shown before the eyes with visual vividness". What transforms a description into an ekphrasis, that is, what conjures up for the reader or listener the illusion of an actual object, is the ideal of visual vividness, or enargeia. An important role here is assigned to the colours and materials of the art work (yellow blossoms, grey hair, dark grapes, wooden cup). There are two kinds of enargeia: the capacity of visualisation inherent in the picture itself, and the same capacity as attained through the verbal effects of the description. The enargeia may be enhanced by descriptions of movements, actions, thoughts and impulses in narratives, as well as by such sound devices as alliteration and assonance. Is the art work described real or imaginary? While the description does echo real iconographic types and aesthetic tendencies, it is at the same time a creative literary construct drawing on the rhetorical and philosophical theory of imaginative depiction, phantasia. The "pictorial realism" of the description follows the trends of the Late Classical period. As the audience is assumed to be familiar with the content, the description focuses on the essential elements of the story. Moreover, Theocritus' description is not limited to the "visual" aspect of a verbal artwork but also comments on the narrative. In this context, the description may be read as a metaphor for vitality - in contrast to death, as chosen by Daphnis.
Keywords: anargeia; ekfraza; grška književnost; helenizem; likovne umetnine; Teokrit